2010
DOI: 10.1111/j.1365-2621.2010.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sesame protein isolate in partial replacement of milk protein on the rheological, textural and microstructural characteristics of fresh cheese

Abstract: Soft cheeses were manufactured from bovine milk with the addition of 0-12% sesame protein isolate (SPI) were utilised to investigate rheology, texture and microstructure at different stages of cheese making. SPI addition reduced the speed of milk fermentation, kappa-casein proteolysis of rennet and elongated the time of cheese curd formation. Renneted milk storage modulus G¢ 60min was decreased and coagulation time increased with increasing SPI content. Low SPI supplements (4% and 8%) enhanced the hardness, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…Especially in dairy products, the structure of the gel composed of plant proteins, casein and whey protein is not fully understood. Certain authors have reported that the firmness or hardness of different fermented products increased with weak supplements of plant ingredients: up to 3% lentil flour in yoghurt (Zare et al, 2011), up to 8% sesame protein isolate in soft cheese (Lu, Schmitt, & Chen, 2010), up to 3% soy protein in rennet curd formation "Mozzarella" (Hsieh, Yun, & Rao, 1993). On the contrary, greater pulse supplementation leads to a more fragile coagulum and so to a lesser degree of firmness or "hardness": 20% soy protein in rennet curd formation (Lee & Marshall, 1979), 12%…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…Especially in dairy products, the structure of the gel composed of plant proteins, casein and whey protein is not fully understood. Certain authors have reported that the firmness or hardness of different fermented products increased with weak supplements of plant ingredients: up to 3% lentil flour in yoghurt (Zare et al, 2011), up to 8% sesame protein isolate in soft cheese (Lu, Schmitt, & Chen, 2010), up to 3% soy protein in rennet curd formation "Mozzarella" (Hsieh, Yun, & Rao, 1993). On the contrary, greater pulse supplementation leads to a more fragile coagulum and so to a lesser degree of firmness or "hardness": 20% soy protein in rennet curd formation (Lee & Marshall, 1979), 12%…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…Texture profile analysis (TPA) of cheese samples was performed using TMS‐PRO instruments (Food Technology Corporation, Sterling, VA) at room temperature (20 ± 2C) on cylinders, 10 mm in diameter by 10 mm in height (Lu et al . 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Each measurement was carried out in triplicates. Texture profile analysis (TPA) of cheese samples was performed using TMS-PRO instruments (Food Technology Corporation, Sterling, VA) at room temperature (20 Ϯ 2C) on cylinders, 10 mm in diameter by 10 mm in height (Lu et al 2010). Samples were cut from the central part of cheese pieces with a cheese sampler, and held at 20 Ϯ 2C for 30 min.…”
Section: Rheology and Instrumental Texture Measurementmentioning
confidence: 99%
See 2 more Smart Citations